1977
DOI: 10.1002/aic.690230305
|View full text |Cite
|
Sign up to set email alerts
|

Flow of slurries in pipelines

Abstract: Pressure drop correlations for flow of slurries in pipelines were developed for each of the following four flow regimes: flow with a stationary bed, saltation flow, heterogeneous flow, and homogeneous flow. A total number of 2 848 data points, comprised of 1912 collected from the published literature together with 936 taken using our own test pipelines and relating to ranges of the pertinent variables extensive enough to span all four flow regimes were used as the basis of these correlations. Also, these data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(96 citation statements)
references
References 13 publications
3
90
0
Order By: Relevance
“…Numbers of such phenomenological modeling have been proposed by Wilson [27,28] Wilson and Pugh [29], Roco and Shook [20,21], Doron et al [7] and many others.…”
Section: Background and Importance Of Pressure Dropmentioning
confidence: 97%
See 1 more Smart Citation
“…Numbers of such phenomenological modeling have been proposed by Wilson [27,28] Wilson and Pugh [29], Roco and Shook [20,21], Doron et al [7] and many others.…”
Section: Background and Importance Of Pressure Dropmentioning
confidence: 97%
“…In spite of the lack of detailed fundamental knowledge required for the formulation and modeling of multiphase turbulent flows, the need to predict slurry behavior handled in various industries has motivated work, aimed at obtaining approximate solutions. Various investigations ( [7,9,13,26,27], etc.) have tried to show and propose correlation relating pressure drop with other parameters of solid-liquid flow, namely solids density, liquid density, particle size, concentration, pipe diameter, viscosity of flowing media, velocity of suspension etc.…”
Section: Background and Importance Of Pressure Dropmentioning
confidence: 99%
“…4 illustrate rheological behaviors, especially at low shear rates. Many studies have indicated that dispersions of acicular particles have a larger viscosity than those of spherical particles (12)(13)(14)(15). This confirmed that the viscosity and the degree of shear-thinning increase rapidly when acicular -FeOOH particles are formed at the initial to middle reaction stages.…”
Section: Rheological Behaviormentioning
confidence: 99%
“…This complexity may lead erroneous results when calculating friction pressure losses for slurry flow to calculate the resulted bottom hole treating pressure and hence the net pressure. Several researchers [3][4][5][6] provided a comprehensive review and background on slurry flow. However, much of the previous research be focused on the flow of solids in Newtonian fluids and numerous correlations were made available for predicting the slurry relative viscosity which can be used for frictional pressure losses estimation.…”
Section: Introductionmentioning
confidence: 99%